2017
DOI: 10.1117/12.2252480
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent OCT imaging of stimulus evoked retinal neural activation and hemodynamic responses

Abstract: It is well established that major retinal diseases involve distortions of the retinal neural physiology and blood vascular structures. However, the details of distortions in retinal neurovascular coupling associated with major eye diseases are not well understood. In this study, a multi-modal optical coherence tomography (OCT) imaging system was developed to enable concurrent imaging of retinal neural activity and vascular hemodynamics. Flicker light stimulation was applied to mouse retinas to evoke retinal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…For arterioles and venules, when measuring RBC velocity responses to flicker stimulation, we have shown that individual capillary RBC velocities vary across capillaries (either increasing or decreasing), differing from arterioles and venules, which show a consistent response. 10 , 24 , 41 Unlike other studies that have found increases in RBC velocity in larger retinal vessels during flicker stimulation, 42 44 our capillary measurements in this study showed an increase in RBC velocity in only three out of the five subjects, although from a larger sample we found on average that capillary flow increased by about the same amount as arteriole flow, but the change was not statistically significant, in part due to the variability in capillary measurements. 24 …”
Section: Discussioncontrasting
confidence: 75%
“…For arterioles and venules, when measuring RBC velocity responses to flicker stimulation, we have shown that individual capillary RBC velocities vary across capillaries (either increasing or decreasing), differing from arterioles and venules, which show a consistent response. 10 , 24 , 41 Unlike other studies that have found increases in RBC velocity in larger retinal vessels during flicker stimulation, 42 44 our capillary measurements in this study showed an increase in RBC velocity in only three out of the five subjects, although from a larger sample we found on average that capillary flow increased by about the same amount as arteriole flow, but the change was not statistically significant, in part due to the variability in capillary measurements. 24 …”
Section: Discussioncontrasting
confidence: 75%
“…As such, studies using multifunction OCT angiography show that this technique allows for the assessment of flicker evoked hemodynamic responses of individual layers of the retina. [17, 18] Alternatively, dual-beam bidirectional Doppler Fourier-domain has been used to quantify flicker evoked hemodynamic changes in both animal and human experiments. [19, 20] However, the latter techniques are currently not commercially available and therefore only limited to specialized research centers.…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods available to elicit a dynamic response in the retinal microvasculature. The handgrip test and hyperoxic conditions have been previously used to induce retinal vasoconstriction ( 27 , 30 , 51 , 52 ), while the flicker test and hypoxia have been reported to illicit a vasodilatory response ( 27 , 30 , 53 ). Currently, these techniques are limited to research use, however they may have clinical applicability with standardization of methods and reporting of test findings.…”
Section: Discussionmentioning
confidence: 99%